(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
The review of the New World carried out by the French Renaissance writer Michel de Montaigne in some of his most famous essays provided a picture of human condition that broke with the Aristotelian paradigm held by the Spanish humanist Juan Ginés de Sepúlveda and other authors. Montaigne, using the same texts that most of the scholastic scholars of his time used, takes distance from the dominant peripatetic view of man (christianized during the Middle Ages), showing an alternative perspective that we could qualify as radically Modern.